Corydoras ortegai, a new species of corydoradine catfish from the lower río Putumayo in Peru (Ostariophysi: Siluriformes: Callichthyidae) - Marcelo R. Britto; Flávio C. T. Lima; Max H. Hidalgo (Neotropical Ichthyology)
A new species of Corydoras, C. ortegai, is described from tributaries of the lower course of río Putumayo in Peru, close to the border with Brazil and Colombia. The new species seems to be related to Corydoras reynoldsi, C. weitzmani, C. panda, and C. tukano, all of which share a pattern composed of uniform light ground color on body, dark bar ("mask") across orbit, and one or two large rounded blotches midlaterally on trunk. Corydoras ortegai is easily distinguished from these species, except C. panda, mainly by the absence of a midlateral trunk blotch at the dorsal-fin level, and the rounded shape of the midlateral trunk blotch at the adipose-fin level. Corydoras ortegai differs from C. panda by its greater number of lateral body plates, lack of dorsal-fin blotch, scattered chromatophores surrounding midregion of cleithrum, caudal fin with series of small blotches restricted to rays, slenderer body, and narrower intercleithral area. Corydoras ortegai belongs to a putatively monophyletic assemblage of Corydoras that occurs mainly in the Western Amazon basin, C. tukano excepted. The occurrence of Corydoras tukano in the rio Tiquié (upper Negro basin) and its putative sister species, C. ortegai, in the western Amazon, together with similar distribution patterns shared by other groups of fishes, suggest a biogeographic relationship between these areas.